PFIN, 7th Edition - Randall Billingsley; Lawrence J. Gitman; Michael D. Joehnk (Cengage Learning, 2019)
PFIN7 has numerous features that relate personal finance to students' day-to-day lives. These include "You Can Do It Now" on personal financial actions students can take now, "Financial Impact of Personal Choices" that illustrates the financial effects of key personal decisions, "Financial Planning Tips", "Behavior Matters" on the behavioral aspects of personal finance, and "Planning Over a Lifetime" on financial planning over the life cycle. PFIN7 helps instructors by allowing them to present students with essential decision-making frameworks and up-to-date information on key topics that include buying a home or car, setting up and maintaining a budget, handling student loans, insuring your life, health and property, investing to meet goals like retirement, and doing your taxes. All data and figures are updated through the second quarter of 2018. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.